Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 2 - Equations, Inequalities, and Problem Solving - 2.2 Using the Principles Together - 2.2 Exercise Set: 93

Answer

$a=2$

Work Step by Step

Using the properties of equality, the solution to the given equation, $ a+(a-3)=(a+2)-(a+1) $, is \begin{array}{l} a+a-3=a+2-a-1 \\\\ 2a-3=1 \\\\ 2a=1+3 \\\\ 2a=4 \\\\ a=\dfrac{4}{2} \\\\ a=2 .\end{array} CHECKING: \begin{array}{l} 2+(2-3)=(2+2)-(2+1) \\\\ 2+(-1)=(4)-(3) \\\\ 1=1 \text{ (TRUE)} .\end{array} Hence, the solution is $ a=2 $.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.